Cytokine levels in children and adults with wheezing and asthma show specific patterns of variability over time. (15th December 2020) - Weckmann, M.; Thiele, D.; Liboschik, L.; Bahmer, T.; Pech, M.; Dittrich, A.‐M.; Fuchs, O.; Happle, C.; Schaub, B.; Ricklefs, I.; Rabe, K. F.; von Mutius, E.; et al.
Summary: Levels of cytokines are used for in‐depth characterization of patients with asthma; however, the variability over time might be a critical confounder. To analyze the course of serum cytokines in children, adolescents and adults with asthma and in healthy controls and to propose statistical methods to control for seasonal effects. Of 532 screened subjects, 514 (91·5%) were included in the All Age Asthma Cohort (ALLIANCE). The cohort included 279 children with either recurrent wheezing bronchitis (more than two episodes) or doctor‐diagnosed asthma, 75 healthy controls, 150 adult asthmatics and 31 adult healthy controls. Blood samples were collected and 25 μl serum was used for analysis with the Bio‐Plex Pr human cytokine 27‐Plex assay. Mean age, body mass index and gender in the three groups of wheezers, asthmatic children and adult asthmatics were comparable to healthy controls. Wheezers (34·5%), asthmatic children (78·7%) and adult asthmatics (62·8%) were significantly more often sensitized compared to controls (4·5, 22 and 22·6%, respectively). Considering the entire cohort, interleukin (IL)‐1ra, IL‐4, IL‐9, IL‐17, macrophage inflammatory protein (MIP)‐1‐ α and tumor necrosis factor (TNF)‐ α showed seasonal variability, whereas IL‐1β, IL‐7, IL‐8, IL‐13, eotaxin, granulocyte colony‐stimulating factor (G‐CSF), interferon gamma‐induced protein (IP)‐10, MIP‐1 β and platelet‐derived growth factor (PDGF)‐BB did not. Significant differences between wheezers/asthmatics and healthy controls were observed for IL‐17 and PDGF‐BB, which remained stable after adjustment for the seasonality of IL‐17. Seasonality has a significant impact on serum cytokine levels in patients with asthma. Because endotyping has achieved clinical importance to guide individualized patient‐tailored therapy, it is important to account for seasonal effects. Abstract : Cytokines as biomarkers for asthma underly seasonal variability, as investigated in the large German cohort ALLIANCE. We propose two methods to account for the seasonality and check whether this influences the differences between asthmatics or wheezers and healthy controls for each cytokine.